Synchronic and diachronic readings on Jeremiah Scroll: in search of a methodology for Jeremianic studies. Part 1 - Yan, Anderson (Vox Scripturae - Revista Teológica Internacional, 2016)
This paper challenges the dichotomy between synchronic and diachronic readings of Jeremiah scroll, proposing a methodology which combines both approaches. The essay starts by clarifying the definitions of synchronic and diachronic in biblical studies, followed by the presentation of the sources using text criticism and literary analysis. The paper argues that although the textual-literary evidence strongly supports diachronic approach, it is not sufficient to date the text or to answer synchronic questions.